Glucagon-like peptide 1 receptor-mediated stimulation of a GABAergic projection from the bed nucleus of the stria terminalis to the hypothalamic paraventricular nucleus - Nadya Povysheva; Huiyuan Zheng; Linda Rinaman (Neurobiology of Stress, 2021)
We previously reported that GABAergic neurons within the ventral anterior lateral bed nucleus of the stria terminalis (alBST) express glucagon-like peptide 1 receptor (GLP1R) in rats, and that virally-mediated “knock-down” of GLP1R expression in the alBST prolongs the hypothalamic-pituitary-adrenal axis response to acute stress. Given other evidence that a GABAergic projection pathway from ventral alBST serves to limit stress-induced activation of the HPA axis, we hypothesized that GLP1 signaling promotes activation of GABAergic ventral alBST neurons that project directly to the paraventricular nucleus of the hypothalamus (PVN). After PVN microinjection of fluorescent retrograde tracer followed by preparation of ex vivo rat brain slices, whole-cell patch clamp recordings were made in identified PVN-projecting neurons within the ventral alBST. Bath application of Exendin-4 (a specific GLP1R agonist) indirectly depolarized PVN-projecting neurons in the ventral alBST and adjacent hypothalamic parastrial nucleus (PS) through a network-dependent increase in excitatory synaptic inputs, coupled with a network-independent reduction in inhibitory inputs. Additional retrograde tracing experiments combined with in situ hybridization confirmed that PVN-projecting neurons within the ventral alBST/PS are GABAergic, and do not express GLP1R mRNA. Conversely, GLP1R mRNA is expressed by a subset of neurons that project into the ventral alBST and were likely contained within coronal ex vivo slices, including GABAergic neurons within the oval subnucleus of the dorsal alBST and glutamatergic neurons within the substantia innominata. Our novel findings reveal potential GLP1R-mediated mechanisms through which the alBST exerts inhibitory control over the endocrine HPA axis.